Digital trade facilitation: Paperless trade in regional trade agreements - Yann Duval; Kong Mengjing (Asian Development Bank Institute (ADBI), 2017)
Digital trade facilitation refers to the application of modern information and communication technologies (ICTs) to simplify and automate international trade procedures. It is rapidly becoming essential to maintaining trade competitiveness and enabling effective participation in cross-border e-commerce. This paper examines the extent to which measures aimed at dematerializing trade data and documents and enabling their electronic exchange, commonly referred to as paperless trade measures, are included in regional trade agreements (RTAs), including in the Trans-Pacific Partnership and ASEAN agreements. Such measures are most commonly found in RTA chapters on e-commerce or in those dedicated to Customs and trade facilitation. Their number is found to have doubled in RTAs between 2005-8 and 2013-16 at the global level. Most recent RTAs also contain more and deeper paperless trade provisions than those featured in the WTO Trade Facilitation Agreement. A more detailed analysis of paperless trade measures included in selected RTAs in Asia and the Pacific confirms that the coverage of RTAs of paperless trade issues has become extensive, covering increasingly specific areas such as electronic certificates of origins and sanitary and phytosanitary certificates. In that context, the new Framework Agreement on Facilitation of Cross-Border Paperless Trade in Asia and the Pacific can be expected to provide a useful tool for harmonized implementation of many of these provisions.
Keywords: F10; F13; F15; O14; 330; regional trade agreements; paperless trade; trade facilitation; digital trade; electronic certificates; trade integration; regional cooperation; free trade agreements; cross-border paperless trade; e-commerce; treaty; RTAs; WTO; ESCAP; Asia; Pacific